Forecasting Tingkat Inflasi Year-on-Year Indonesia Dengan Metode Weighted Moving Average (WMA) - Wigid Hariadi; Sulantari Sulantari (UJMC (Unisda Journal of Mathematics and Computer Science), 2022)
Abstract. The weighted moving average (WMA) method is a method of calculating data forecasting values through moving average values that are given different weights for each time period. The Covid-19 pandemic has had a considerable impact on the State of Indonesia. Not only from the health sector of the residents, but also the economic sector of the residents was also quite badly affected. This economic impact can be felt from the rising prices of goods needed by the community and in addition to the increasingly deteriorating financial conditions of the community. Not yet recovered due to the Covid-19 pandemic, there was a war between Russia and Ukraine in 2022 which helped balance the inflation rate in Indonesia. This is because the war made the price of fuel and wheat commodities increase more and more expensive. This inflation rate is one indicator of economic growth in a country, and is very influential on the economic growth of a country. Because of this, it is important for us to be able to know the projection (data forecast) of the inflation rate for the next several periods. This is intended so that related parties can prepare the right strategy in dealing with the inflation rate. From the results of the study, it was concluded that a good Weighted Moving Average model for predicting Indonesia's year on year inflation rate is a 3rd order WMA model with a weight of 0.65; 0.2; 0.15, with an MSE value of 0.2632, MAD of 0.3549, and a MAPE value of 0.1114 or (11.14%). Indonesia's YoY inflation forecast for the next 4 months, namely: In December 2022 it was 5.56, January 2023 it was 5.55, February 2023 it was 5.53, and in March 2023 it was 5.54. Keywords: Weighted Moving Average, WMA, Inflation. Abstrak. Metode weighted moving average (WMA) adalah metode menghitung nilai peramalan data melalui nilai rata-rata bergerak yang diberikan bobot yang berbeda untuk tiap-tiap periode waktunya. Pandemi covid-19 memberikan dampak yang cukup besar bagi Negara Indonesia. Tidak hanya dari sektor kesehatan warganya, namun juga sektor perekonomian warga juga ikut terdampak cukup parah. Dampak ekonomi ini dapat dirasakan dari naiknya harga barang-barang kebutuhan masyarakat dan di tambah lagi kondisi keuangan masyrakat yang semakin memburuk. Belum pulih akibat pandemic covid-19, terjadi peristiwa perang antara Rusia dengan Ukraina pada tahun 2022 yang ikut menymbang Tingkat Inflasi di Indonesia. Hal ini disebabkan karena perang tersebut membuat harga BBM dan komoditas gandum meningkat semakin mahal. Tingkat inflasi ini menjadi salah satu indicator pertumbuhan ekonomi di suatu Negara, dan sangat berpengaruh terhadap pertumbuhan ekonomi suatu Negara. Karena hal itu, penting kiranya kita untuk dapat mengetahui proyeksi (peramalan data) tingkat inflasi untuk beberapa periode kedepan. Hal ini bertujuan agar pihak terkait dapat mempersiapakan strategi yang tepat dalam menangani laju tingkat inflasi. Dari hasil penelitian, diperoleh kesimpulan bahwa Model Weighted Moving Average yang baik untuk memprediksi nilai inflasi year on year Indonesia adalah model WMA orde 3 dengan Bobot 0.65; 0.2; 0.15, dengan nilai MSE sebesar 0.2632, MAD sebesar 0.3549, dan nilai MAPE sebesar 0.1114 atau (11.14%). Forecasting inflasi YoY Indonesia selama 4 bulan berikutnya, yaitu: Pada bulan Desember 2022 sebesar 5.56, Januari 2023 sebesar 5.55, Februari 2023 sebesar 5.53, dan pada Maret 2023 sebesar 5.54. Kata kunci: Weighted Moving Average, WMA, inflasi.